Der letzte Versuch des Deutschen Ordens zur Rückkehr nach Ungarn (1702–1731) - Pósán, László (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2016)
The Teutonic Knights’ Last Attempt at Returning to Hungary (1702–1731) Subsequent to the expulsion of the Turks the Teutonic Knights made a last attempt (1702–1731) at returning to Hungary after its abortive attempts in medieval times (1211–1228 and 1429–1432). Emperor Leopold I sold the Jazygian and the two Cumanian districts to the Order of Knights, who had participated in the anti-Turkish war form 1664 onwards. The Jazygian and Cumanian districts enjoyed privileges from medieval times on; being directly subordinate to the crown, the inhabitants had never been burdened by dues to the landed overlords. The population in the districts and the Hungarian estates at large promptly protested against the sale, but the Teutonic Order was unable to come into possession of the districts, for an anti-Habsburg uprising of the Hungarian noble estates broke out in 1703 led by the aristocrat Ferenc Rákóczi 2nd while the Imperial military were engaged in a war against France in the West. But the peace treaty putting an end to the uprising in 1711 did not confirm the position of the Knights, for the Emperor restored the Hungarian estates into their privileges and the Act of 1715 ruled that the transaction of 1702 had been unlawful and the districts should regain their liberties on condition that the estates pay back the purchase price the Knights had paid. This, however, did not materialize owing to the renewed warfare againsts the Turks. With regard to a possible compensation, the Teutonic Order did not implement any settlement or any economic investment in the Jazyigian or Cumanian districts, nor did it draw any profit from them. In 1731, the Grand Master sold the title to the Jazygian and Cumenian districts to the House of Invalids in Pest and the Teutonic Order left Hungary for good.